PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PERUSAHAAN - Mei Indrawati (UMSurabaya Publishing, 2007)
The aim of this writing is as the matter of consideration for company, especially for SDM superintendent in giving motivation and paying attention to working area.Based on testing of hypothesis which explain that there is influence collectively or free variable simultaneous (motivation and working area) to variable trussed (working achievement) using doubled linier regression analyzes; conclude that there is significant influence.Based on testing of hypothesis which explain that there is partially influence free variable (motivation and working area) to variable trussed (working achievement) using doubled linier regression analyzes, conclude that there is significant influence.Partial correlation amount between motivation variable and working achievement variable equal to 0,584; partial correlation amount between working area variable and working achievement variable equal to 0,755. So, can be concluded that working area variable has the influence that more dominant to working achievement if compared with motivation.